Treatment of Juveniles in the Wisconsin Criminal Court System - Wolf, Saul; Martin, Justin; Campbell, Bradley; Boggs, Breann (My University, 2008)
Seventeen-year-olds accused of criminal offenses in Wisconsin have been under the jurisdiction of the adult court system since 1995, when the court system?s treatment of juveniles was changed dramatically. This report provides evidence that legislators should re-examine Wisconsin laws waiving juveniles into adult court and examines alternatives based on the goals of justice, equity, efficiency, operability, and scientific validity.
For PA 869: Public Affairs Workshop, Domestic Issues